Boosting Understanding and Identification of Scientific Consensus Can Help to Correct False Beliefs. (October 2021) - van Stekelenburg, Aart; Schaap, Gabi; Veling, Harm; Buijzen, Moniek
Some people hold beliefs that are opposed to overwhelming scientific evidence. Such misperceptions can be harmful to both personal and societal well-being. Communicating scientific consensus has been found to be effective in eliciting scientifically accurate beliefs, but it is unclear whether it is also effective in correcting false beliefs. Here, we show that a strategy that boosts people's understanding of and ability to identify scientific consensus can help to correct misperceptions. In three experiments with more than 1, 500 U.S. adults who held false beliefs, participants first learned the value of scientific consensus and how to identify it. Subsequently, they read a news article with information about a scientific consensus opposing their beliefs. We found strong evidence that in the domain of genetically engineered food, this two-step communication strategy was more successful in correcting misperceptions than merely communicating scientific consensus. The data suggest that the current approach may not work for misperceptions about climate change.